The impact of artificial intelligence and entrepreneurship education on entrepreneurial intention: Strengthening the entrepreneurial intention of economics students in Hai Phong city - Duyen, Vu Thi Mai; Thanh, Le Chi; Ngoc, Ha Bich; Duong, Phan Huy (Edelweiss Applied Science and Technology, 2025)
The Vietnamese government is implementing numerous changes in economic policies, which pose challenges to increasing the entrepreneurial intentions of economics students. Entrepreneurship education plays a crucial role in fostering motivation to pursue business ventures. In fact, further research is necessary to understand the factors influencing the effectiveness of entrepreneurship education for economics students. This study aims to measure the impact of entrepreneurship education on the entrepreneurial intentions of economics students in Hai Phong city and to examine the mediating role of Artificial Intelligence (AI). Data were collected through surveys from 428 students enrolled in business administration or economics programs across several universities and analyzed using Structural Equation Modeling (SEM). The findings indicate that entrepreneurship education has a positive and significant effect on entrepreneurial intention. Additionally, AI serves as a significant mediating factor, enhancing the influence of entrepreneurship education on entrepreneurial intention. The results demonstrate that integrating AI tools into entrepreneurship education can strengthen students’ entrepreneurial mindset and motivation. This study provides empirical evidence on the mediating role of AI in entrepreneurship education and offers practical insights for optimizing teaching strategies with emerging technologies, thereby nurturing a new generation of students in the digital age.